Creativity and Cognition 2021
DOI: 10.1145/3450741.3465258
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising sound-driven design: an exploratory discourse analysis

Abstract: Sound-driven design is an emerging, human-centered design practice informed by technology and listening in the multisensory dimension of interaction. In this paper we present a discourse analysis approach aimed at qualitatively understanding the constituent concepts of such a practice, by means of semi-structured interviews with sound designers, design researchers, engineers and expert users in the context of critical care. Preliminary results show that sound-driven design is inherently embodied, situated, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…For compositions, this can be seen in the form of physical prototypes handled by users to produce or trigger soundscapes. This can be related to Monache et al 's [51] discourse analysis on sound-driven design as "[...] inherently embodied, situated, and participatory".…”
Section: Hybrid Approachesmentioning
confidence: 86%
See 1 more Smart Citation
“…For compositions, this can be seen in the form of physical prototypes handled by users to produce or trigger soundscapes. This can be related to Monache et al 's [51] discourse analysis on sound-driven design as "[...] inherently embodied, situated, and participatory".…”
Section: Hybrid Approachesmentioning
confidence: 86%
“…Within recent years, sound has taken up a prominent role in a wide range of HCI-related works. This includes expanding the focus on embodiment, e.g., to use sounds to simulate co-located experiences [109], as well as for a proposed 'sound-driven design' approach to externalise tacit expert knowledge [51], to name just two examples. In this paper, we focus specifcally on soundscapesan area with a rich history outside of HCI but which is currently also expanding within our community due to increased audio technological possibilities and the desire to provide immersive and embodied experiences.…”
Section: Sound Design In Hcimentioning
confidence: 99%
“…Recent studies of delle Monache and colleagues [ 9 , 10 ] also demonstrated the permanence of sound-action coupling in the way people express their experiences with sounds. In previous research, Özcan [ 69 ] demonstrated the varying degrees of sound experiences ranging from sensory (dis)pleasure to functional experience of products through sound and to how context shapes users’ emotional responses towards product sounds (see Figure 2 ) [ 70 , 71 , 72 , 73 ].…”
Section: Background Into Listening In Complex Sound Environmentsmentioning
confidence: 99%
“…This approach has indeed been so far instrumental in engineering and design of products and (eco)systems for improved functionality and acceptability. However, in recent studies, delle Monache [ 9 , 10 ] showed that listening-in-action is the primary and core activity when either using sound for completing a task or designing for human-sound interactions. User-centered approaches emphasize the importance of understanding the context of the user and their needs for better designs (e.g., Sleeswijk Visser and Stappers’s work on context mapping [ 11 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The history of sound design can be traced from Greek and Roman theatre to the development of new audio technology and media (radio, television, cinema, games, virtual reality) in the 20th century which generated a great variety of new methods for designing sounds. Recent research taps into this, and related knowledge and creative practice, to inform new methods for functional sound design, such as sonic interaction design and sonification 26,27,28,29 .…”
Section: Basics Of Sound Design and Sonificationmentioning
confidence: 99%